2016
DOI: 10.1038/srep18517
|View full text |Cite
|
Sign up to set email alerts
|

Integration of genomic, transcriptomic and proteomic data identifies two biologically distinct subtypes of invasive lobular breast cancer

Abstract: Invasive lobular carcinoma (ILC) is the second most frequently occurring histological breast cancer subtype after invasive ductal carcinoma (IDC), accounting for around 10% of all breast cancers. The molecular processes that drive the development of ILC are still largely unknown. We have performed a comprehensive genomic, transcriptomic and proteomic analysis of a large ILC patient cohort and present here an integrated molecular portrait of ILC. Mutations in CDH1 and in the PI3K pathway are the most frequent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
143
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(155 citation statements)
references
References 46 publications
9
143
1
1
Order By: Relevance
“…IDC and ILC have distinct histological characteristics and clinical outcomes, and molecular alterations that distinguish these breast cancer variants have been identified (7)(8)(9). Comparison of our data with published comprehensive genomic studies of ILC and IDC revealed that PILC and ILC share many of the significant alterations that are associated with ILC and confirmed molecular differences that distinguish ILC from IDC (7-9) (Figure 2, A and B, and Supplemental Table 5).…”
Section: Identification Of Recurrently Mutated Genes In Pilc Pilc Tusupporting
confidence: 61%
“…IDC and ILC have distinct histological characteristics and clinical outcomes, and molecular alterations that distinguish these breast cancer variants have been identified (7)(8)(9). Comparison of our data with published comprehensive genomic studies of ILC and IDC revealed that PILC and ILC share many of the significant alterations that are associated with ILC and confirmed molecular differences that distinguish ILC from IDC (7-9) (Figure 2, A and B, and Supplemental Table 5).…”
Section: Identification Of Recurrently Mutated Genes In Pilc Pilc Tusupporting
confidence: 61%
“…Other theories on the predilection for the GI tract argued that the unique microenvironment of the gastrointestinal tract potentially allows the proliferation of tumor cells by providing the necessary building blocks for their survival, and the morphology of the tumor cells' shape might cause them to be favorably trapped in the microanatomy of the GI tract [9] . To investigate the molecular process that drives the development of ILC, Michaut et al performed a comprehensive genomic, transcriptomic, and proteomic analyses of a large ILC patient cohort [10] . Mutations in CDH1 and in the phosphoinositide 3-kinase (PI3K) pathway are the most frequent molecular alterations in ILC.…”
Section: Discussionmentioning
confidence: 99%
“…A genomic study examining the invasive lobular carcinoma histologic sub-type, representing about 10-15% of total breast cancers, found that these cancers could be classified in two groups, an immune-related and a hormone-related group (20). Cases in the immune-related group displayed high expression of PD-L1, PD-1 and CTLA-4 in the mRNA level and were more sensitive to DNA-damaging agents.…”
Section: Ctla-4mentioning
confidence: 99%
“…In this regard, a study that used an in silico epitope prediction algorithm proposed that both breast and colorectal cancers present an average of seven to ten human leukocyte antigen (HLA)-A*0201-associated neo-antigens (56). Specifically in the lobular histology sub-type of breast cancer, some lobular carcinomas contain a higher number of somatic mutations than other lobular cancers and have a worse prognosis (20). These could represent an opportunity for therapeutic targeting.…”
Section: Genetic Instability As a Predictor Of Immune Blockade Efficacymentioning
confidence: 99%